Effects of Subcutaneous and Intravenous Recombinant Human Erythropoietin Treatments on Body Iron in Rats - Ahmed Shujaaedin, Hareth Yahya (2009)
Recombinant human erythropoietin (rHuEPO) is used widely in clinical practice for correcting anemia related to renal failure, cancer chemotherapy, HIV infection, premature infants, and chronic diseases. Recombinant human erythropoietin is known to affect body iron status that may result in functional iron deficiency (FlO). Functional iron deficiency is one of the major causes of insufficient response to rHuEPO. Thus rHuEPO treatment must be accompanied with iron supplementation to avoid iron metabolism disorder and to maintain optimal erythropoiesis. The aim of this study was to compare the effect of subcutaneous (s.c.) with the intravenous (i.v.) rHuEPO administration on the body iron status in rats after short-term and long-term treatments. For the short-term experiment, 20 Sprague-Dawley rats were divided into four groups of 5 rats each; s.c. rHuEPO group (s.c. 150 IU rHuEPO/kg/day), control group for s.c. rHuEPO (s.c. 0.40 - 0.44 mL 0.9% saline solution/rat/day), i.v. rHuEPO group (i.v. 150 IU rHuEPO/kg/day), and control group for i.v. rHuEPO (i.v. 0.40 - 0.45 mL 0.9% saline solution/rat/day). The duration of the short-term rHuEPO treatments was 7 days. For the longterm experiment 80 Sprague-Dawley rats were divided into four groups of 20 rats each ; s.c. rHuEPO group (s.c. 450 IU rHuEPO/kg/wk), control group for s.c. rHuEPO (s.c. 0.40 - 0.50 mL 0.9% saline solution/rat/wk), i.v. rHuEPO group (i.v. 450 IU rHuEPO/kg/wk), and control group for i.v. rHuEPO (i.v. 0.40 - 0.50 mL 0.9% saline solution/rat/wk). The duration of the long-term rHuEPO treatments was 8 weeks. Blood samples were drawn at the end of the short-term experiment and at wk 2 , wk 6 and wk 8 in long-term experiment. Erythrocyte (RBC) counts, haemoglobin (Hb) concentrations, haematocrit (HCT) and blood smears for reticulocytosis were used to detect activation of erythropoiesis caused by rHu EPO treatment. Serum Iron (SI), transferrin saturation (TS), unsaturated iron binding capacity (UIBC), total iron binding capacity (TIBC), serum ferritin (SF), stainable liver iron (LI), and bone marrow iron (BMI) were analysed to determine body iron status (BIST). Erythr:oc (p<0 .05) higher in all treatment groups compared to the control groups in both short-term and long-term experiments. The blood smears showed increase in reticulocytes in all treatment groups, while no increase in reticulocytes were observed in the control groups in both short-term and long-term experiments. The SI, TS, and BMI were significantly (p<O.05) lower in the treatment groups of short-term and long-term experiments compared to controls. The TIBC was Significantly (p<O.05) higher in the treatment group of short-term but not in long-term experiment while SF and LI showed no significant (p>O.05) difference between groups except in short-term s.c group. The degree of these changes was greater in the i.v. rHuEPO than in the s.c rHuEPO group both for the short-term and long-term experiments. The effect of rHuEPO on iron parameters that suggested increased iron utilization was more apparent in short-term experiment than long-term experiment. In conclusion, this study suggests that among the effects of rHuEPO administration is increasing erythropoiesis through the utilization of serum and storage irons, and that the effect is more pronounced with i.v. than s.c rHuEPO administration particularly in short-term treatment.